Endoscopic-assisted multi-portal compartmental resection of the masticatory space in oral cancer: Anatomical study and preliminary clinical experience. (June 2021) - Schreiber, Alberto; Mattavelli, Davide; Accorona, Remo; Rampinelli, Vittorio; Ferrari, Marco; Grammatica, Alberto; Tomacelli, Giovanni Leo; Verzeletti, Vincenzo; Fazio, Enrico; Abousiam, Monir; Nebiaj, Aurel; Deganello, Alberto; et al.
Highlights: OSCC may exhibit critical extensions to the masticatory space. Negative margins at the skull base remains the most important prognostic factor. Multi-portal compartmental approach allows full control of tumor margins. Transnasal corridor as an early step allows control of the upper masticatory space. Abstract: Objectives: To present an anatomical cadaver dissection study and our preliminary surgical experience with endoscopic-assisted multi-portal compartmental resection of the masticatory space (MS) in locally advanced oral squamous cell carcinoma (OSCC) of the retromolar area. Materials and methods: Two fresh-frozen cadaver heads were dissected in the Laboratory of Anatomy to define the surgical steps of an endoscopic-assisted multi-portal compartmental approach to the MS. After this preclinical anatomical study, patients affected by locally advanced OSCC originating from the retromolar area with extension to the MS were prospectively enrolled and operated at two Italian referral centers for head and neck cancer between October 2019 and May 2020. Results: Surgical technique of endoscopic-assisted multi-portal compartmental resection of the MS was preclinically defined step by step in 3 phases: transnasal, transoral/trancervical, and multi-portal. Compartmental resection of the MS was successfully completed in all specimens (4 MSs dissected). The surgical technique was subsequently applied in 3 patients affected by primary OSCC of the retromolar area, providing satisfactory results in terms of negative resection margins and local control. Conclusions: Multi-portal compartmental resection of the MS combining the transnasal and transoral/transcervical corridors is technically feasible. Such an approach to the MS in locally advanced OSCC provides different angles of incidence to the target and full control of tumor margins.